Design and performance of autonomous chevron-brace systems with elastomeric-dampers for steel frames. (December 2015) - Gauron, Olivier; Girard, Olivier; Paultre, Patrick; Proulx, Jean
Abstract: This paper presents an innovative use of natural rubber pads for seismic control of multistory low- and medium-rise steel braced frames. Such pads have always been used as supplemental energy dissipation devices in structures that already have their own and independent seismic force resisting system. This paper investigates the use of such devices in series with chevron braces as an autonomous seismic force resisting system, which provides not only additional damping to the structure but also a period shift. The damping and isolation material is a fiber reinforced natural rubber exhibiting strong nonlinear dependence with respect to strain. First, a design procedure based on numerical studies is illustrated for a typical one-story building. Pseudo-linear models of the structures are used for the final evaluation of the seismic response. Cyclic tests on a full scale frame were conducted to calibrate the models and showed the reliability of the autonomous rubber-based system under full loading and real assembly conditions. Then a 1/3-scale 3-story chevron braced steel frame with and without rubber devices was used to evaluate the seismic performances of the system. The application was studied numerically and experimentally through shake table tests of the 1/3 reduced-scale model at different seismic intensities. Results show the efficiency of the system to significantly reduce linear seismic forces induced on the structure without devices. Control of displacements is also achieved but is highly dependant on the initial value of damping in the structure without devices. Highlights: In this study, elastomeric dampers are used as an autonomous seismic force resisting system (SFRS) for steel frames. No other SFRS are provided than the dampers in series with chevron bracings, as opposite to usual applications. The system is shown to be efficient and cost-effective with numerical studies and a practical design procedure is proposed. Experimental devices are tested in real assembly conditions that show the efficiency and the reliability of the SFRS. The study is a rare application of fiber-reinforced natural rubber in earthquake engineering.